2019
DOI: 10.1186/s12887-019-1767-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of acute respiratory infections among under five children attending public hospitals in southern Tigray, Ethiopia, 2016/2017

Abstract: BackgroundAcute Respiratory infection accounts for 94,037000 disability adjusted life years and 1.9 million deaths worldwide. Acute respiratory infections is the most common causes of under-five illness and mortality. The under five children gets three to six episodes of acute respiratory infections annually regardless of where they live. Disease burden due to acute respiratory infection is 10–50 times higher in developing countries when compared to developed countries. The aim of this study was to assess risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 9 publications
5
40
1
2
Order By: Relevance
“…Children who had a history of diarrhea in the past fifteen days were ten times more likely to develop community-acquired pneumonia compared to their counterparts. Similar studies conducted in Urban Areas of Oromia special Zone of Amhara Region, Tigray Ethiopia and Zimbabwe [10,20,21] reported different findings with current findings, the difference might be due to variation in methods. This can be explained by the fact that children who have a concomitant illness like diarrhea may have a lowered immunity, making them more susceptible to diseases like pneumonia.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Children who had a history of diarrhea in the past fifteen days were ten times more likely to develop community-acquired pneumonia compared to their counterparts. Similar studies conducted in Urban Areas of Oromia special Zone of Amhara Region, Tigray Ethiopia and Zimbabwe [10,20,21] reported different findings with current findings, the difference might be due to variation in methods. This can be explained by the fact that children who have a concomitant illness like diarrhea may have a lowered immunity, making them more susceptible to diseases like pneumonia.…”
Section: Discussionsupporting
confidence: 45%
“…Almost half of the pneumonia deaths were associated with air pollution. The impact of indoor air pollution kills more children globally than outdoor air pollution [10,11]. Outdoor air pollutants (PM10, NO2, O3, CO, and SO2), diurnal temperature range, and tree and weed.…”
mentioning
confidence: 99%
“…Some of the factors identified as influencing morbidity among children include maternal education, maternal age, child's nutritional status, child's age, household wealth, residence, handwashing, sanitation, water source, use of insecticide-treated nets and exposure to information on morbidity, among others. [6][7][8][9][10][11][12][13][14][15][16][17] For instance, some studies showed that diarrhoea infection is higher among children whose mothers have no education and do not wash their hands after using the toilet. Other studies revealed that malaria and acute respiratory infection are higher among children in rural setting and children whose mothers are 16-17 and 28-33 years of age.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…In Ethiopia, there are 55 deaths per 1000 live births in children under-five due to acute respiratory infection, placing it among the world’s highest mortality rates [ 19 ]. Prior studies indicated that maternal age, residence, maternal hand hygiene information [ 20 ], maternal literacy, smoking, use of animal dung as a fuel source, nutritional status [ 21 ], absence of a separate kitchen, and lack of windows were significantly associated with acute respiratory infections [ 22 25 ].…”
Section: Introductionmentioning
confidence: 99%